2004
DOI: 10.1074/jbc.m404114200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ubiquitin Protein Ligase Activity in c-Cbl by Phosphorylation-induced Conformational Change and Constitutive Activation by Tyrosine to Glutamate Point Mutations

Abstract: c-Cbl down-regulates receptor tyrosine kinases by conjugating ubiquitin to them, leading to receptor internalization and degradation. The ubiquitin protein ligase activity of c-Cbl (abbreviated as E3 activity) is mediated by its RING finger domain. We show here that the E3 activity of c-Cbl is negatively regulated by other domains present in the amino-terminal half of the protein (the TKB and linker helix domains) and that this negative regulation is removed when the protein is phosphorylated on tyrosine resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
157
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(163 citation statements)
references
References 28 publications
(29 reference statements)
6
157
0
Order By: Relevance
“…It is possible that monoubiquitination of ROMK channels may be required for initiating endocytosis induced by stimulation of PTK activity. Interestingly, it has been demonstrated that activity of c-Cbl, an E3 ubiquitin ligase with RING finger domain, is stimulated by tyrosine phosphorylation (41). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that monoubiquitination of ROMK channels may be required for initiating endocytosis induced by stimulation of PTK activity. Interestingly, it has been demonstrated that activity of c-Cbl, an E3 ubiquitin ligase with RING finger domain, is stimulated by tyrosine phosphorylation (41). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The domain is required for recruitment of E2 enzymes, and functions together with the linker sequence that connects the TKB domain and the RING finger domain in this recruitment (Joazeiro et al, 1999;Levkowitz et al, 1999;Yokouchi et al, 1999;Zheng et al, 2000). The E3 activity is regulated by phosphorylation of residues Y368 and Y371 in c-Cbl, and phosphorylation probably results in conformational changes in c-Cbl favoring E3 activity Kassenbrock and Anderson, 2004). Additionally, c-Cbl activity is proposed to be (Yokouchi et al, 2001).…”
Section: Ubiquitination As Internalization Signal For Egfrmentioning
confidence: 99%
“…Notable targets for c-Cbl-mediated ubiquitination are Lck [9], Vav [10], Fyn [11][12][13], , as well as the already mentioned TCR/ CD3-complex. c-Cbl itself is activated by tyrosine phosphorylation on several residues, most importantly Y700, Y731 and Y774 [13,[15][16][17]. These residues are not, however, substrates of Lck or but of Fyn and Syk [13,16,18,19], which are activated directly or indirectly by Lck [20].…”
mentioning
confidence: 99%